Avoiding Glenoid Baseplate Fixation Failure by Altering Surgical Technique for Varying Bone Densities. Issue 3 (14th July 2022) - Achors, Kyle; Diaz, Miguel A.; Simon, Peter; Hill, Brent; Christmas, Kaitlyn N.; Cronin, Kevin J.; Frankle, Mark A.
Abstract : Background: Glenoid baseplate failure is one of the causes of revision and poor outcomes in reverse shoulder arthroplasty (RSA). The objective of this study was to determine whether alterations in surgical technique can improve time-zero fixation of the baseplate in varying bone densities. A secondary objective was to identify whether preoperative radiographic glenoid sclerosis width was associated with the implementation of these techniques. Methods: This study included a biomechanical analysis and a retrospective radiographic review. The biomechanical portion describes 2 alterations to the standard surgical technique (under-preparation [A1] or over-preparation [A2] of the central screw pilot hole) and determined their torque-compression relationship via bone-substitute blocks with varying densities. Patients who underwent the described technical alterations were identified from a registry database of primary RSAs performed between 2007 and 2020. These patients were matched to patients who underwent the standard surgical technique, and preoperative radiographs were compared. Interrater reliability testing was performed to determine reproducibility. Results: With respect to the biomechanical arm, the average compressive force of the baseplate in the low-density block model when using the standard technique was 112 N compared with 300 N for the A1 technique (p = 0.01). In the high-density bone model, the standard technique resulted in failure to seat the baseplate, or screw breakage. Performing the A2 technique, the baseplate was seated without failure, with an average compressive force of 450 N. In the clinical arm, retrospective intraoperative video review for use of the alternative techniques found 20 shoulders in the "low-density" cohort and 21 in the "high-density" cohort. There was a significant difference in the glenoid sclerosis thickness between the experimental and matched control groups in our "high-density" cohort (p = 0.0014). The interrater reliability coefficient was found to be 0.69 for the "low-density" glenoid sclerosis thickness measurement and 0.92 for the "high-density" measurement. Conclusions: In low- and high-density bone models, alterations in surgical technique significantly improved compression and improved the ability to successfully seat the glenoid baseplate. Preoperative radiographs can assist in indicating the alternative technique in the sclerotic glenoid. Clinical Relevance: Utilization of these techniques intraoperatively will improve time-zero fixation of the glenoid baseplate and potentially avoid failure of fixation.